Academic Efficacy Scale of Junior High School Students in Indonesia - Arviani, Sari; Naqiyah, Najlatun; Rusijono, Rusijono; Nursalim, Mochamad; Budiyanto, Budiyanto; Purwoko, Budi; Sartinah, Endang Pudjiastuti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the effectiveness of an academic self-efficacy instrument for junior secondary school students in Indonesia. This research is important to understand the extent to which students at the junior high school level feel confident in facing academic demands. The type of research in this study used a quantitative approach. The population obtained amounted to 564 eighth-grade students from several provinces in Indonesia. The sampling technique used was convenience sampling, and a sample size of 300 students was determined. Primary data in this study were obtained from the results of students' instrument answers with the filling method circling the most appropriate answer. At the same time, secondary data is obtained from searching journals related to the research. The data collection technique was a fill-in sheet given to 300 grade 8 students in several provinces in Indonesia. Then, the data analysis used was quantitative data analysis carried out by descriptive analysis and verification analysis (hypothesis testing with t-test). Furthermore, based on the data obtained from junior high school students, the instrument was tested for validity and reliability using SPSS version 25. Based on the results of the study, it was found that the instrument used to measure the academic self-efficacy of junior high school students in Indonesia has good validity and reliability. The instrument consists of 49 valid items and has a reliability coefficient of 0.861. Then, to determine the effectiveness of the instrument made, a t-test was conducted, and obtained the result that H0 was rejected, which means that the instrument is effective in measuring academic self-efficacy for junior high school students in Indonesia. Thus, it can be concluded that the instrument is effective in measuring the academic self-efficacy of junior high school students in Indonesia.